New Perspectives in Glioblastoma: Nanoparticles-based Approaches - Luciano, Rosa; Battafarano, Giulia; Saracino, Rossana; Rossi, Michela; Perrotta, Antonio; Manco, Melania; Muraca, Maurizio; Del Fattore, Andrea (Current Cancer Drug Targets, 2017)
Glioblastoma multiforme represents one of the most aggressive tumor of central nervous system. Current therapy includes surgery, radiation and chemotherapy. These treatments are rarely curative and glioma are associated with a poor prognosis. Nanomedicine represents the most innovative branch of medicine since many studies demonstrated great advantage in the diagnosis and therapy of several diseases. In this review we will summarize the results obtained by the use of nanoparticles and extracellular vesicles in glioblastoma. A great interest is raising from these studies that underlined the efficacy and specificity of this treatment for glioma, reducing side-effects associated with conventional therapies.
Keywords: Glioblastoma